“Prisioneros españoles en la Francia napoleónica. Un modelo positivo de los espacios de cautiverio de los suboficiales a través del diario de José Mª Román (1808-1900)” - Zozaya-Montes, Maria (2015)
This analysis of POWs shows a new model of captivity for elite prisoners that has been few studied. It shows how during napoleonic wars the Non Commisioned officers had better conditions than usually are considered in academic field. It is centered in a case study of spanish prisoners in Nancy and Caudebec.